Catastrophic COVID-19 Delta Variant Surge in French West Indies: Report of an ICU Triage Policy*. Issue 1 (8th November 2022) - Pommier, Jean-David; Martino, Frederic; Delamare, Floran; Jarrige, Bruno; Foucan, Tania; Markowicz, Samuel; Valette, Marc; Demoule, Alexandre; Camous, Laurent
Abstract : OBJECTIVES: Here, we report the management of a catastrophic COVID-19 Delta variant surge, which overloaded ICU capacity, using crisis standards of care (CSC) based on a multiapproach protocol. DESIGN: Retrospective observational study. SETTING: University Hospital of Guadeloupe. PATIENTS: This study retrospectively included all patients who were hospitalized for COVID-19 pneumonia between August 11, 2021, and September 10, 2021, and were eligible for ICU admission. Intervention: Based on age, comorbidities, and disease severity, patients were assigned to three groups: Green (ICU admission as soon as possible), Orange (ICU admission after the admission of all patients in the Green group), and Red (no ICU admission). MEASUREMENTS AND MAIN RESULTS: Among the 328 patients eligible for ICU admission, 100 (30%) were assigned to the Green group, 116 (35%) to the Orange group, and 112 (34%) to the Red group. No patient in the Green group died while waiting for an ICU bed, whereas 14 patients (12%) in the Orange group died while waiting for an ICU bed. The 90-day mortality rates were 24%, 37%, and 78% in the Green, Orange, and Red groups, respectively. A total of 130 patients were transferred to the ICU, including 79 from the Green group, 51 from the Orange group, and none from the Red group. Multivariate analysis revealed that among patients admitted to the ICU, death was independently associated with a longer time between ICU referral and ICU admission, the Sequential Organ Failure Assessment score, and the number of comorbidities, but not with triage group. CONCLUSIONS: CSC based on a multiapproach protocol allowed admission of all patients with a good prognosis. Higher mortality was associated with late admission, rather than triage group.